TRANSFORMASI KOMUNIKASI PESAN DAKWAH DI ERA DIGITAL MEDIA SOSIAL MELALUI PLATFORM YOUTUBE - Syahnas, Iin Putri; Setiawati, Nur; Hasriani, Andi; Raehana, Syarifa; Nengsih, Ratika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the transformation of Islamic preaching communication in the digital era through social media, particularly on the YouTube platform. The main issues raised are the forms of Islamic preaching communication transformation and the opportunities and challenges faced in conveying Islamic messages amidst the development of digital technology. This study aims to identify the forms of Islamic preaching communication transformation and explain the opportunities and challenges in utilizing social media as a means of effectively conveying religious messages. The type of research used is descriptive qualitative with a netnographic approach in the study of Islamic preaching communication. Data sources consist of primary and secondary data obtained through virtual observation, documentation, and content analysis on the YouTube platform. The data analysis process is carried out through several stages: data reduction, data presentation, data analysis, and systematic drawing of conclusions to gain a deeper understanding of the phenomenon under study. The results show that the transformation of Islamic preaching communication in the digital era is characterized by changes in communication style, which is more interactive and dialogical, and the use of relaxed language that is easily understood by audiences, especially the younger generation. In addition, Islamic preaching also utilizes attractive visual and audiovisual content to increase the appeal of religious messages. Islamic preaching communication becomes more participatory through interaction features such as comments, likes, and shares. The opportunities for digital da'wah include broad audience reach, easy access to information, and flexibility in time and place. However, challenges also arise, such as the spread of unverified information, the potential for message distortion, and the influence of social media algorithms. Therefore, adaptive, creative, and digital literacy-based da'wah communication strategies are needed to ensure the Islamic message remains authentic, relevant, and can positively impact the wider community.